Heavy Metal Removal from Wastewater using Novel Adsorbent - Kaakani, Manal (2012)
A Master of Science thesis in Civil Engineering by Manal Kaakani entitled, "Heavy Metal Removal from Wastewater using Novel Adsorbent," submitted in January 2012. Thesis advisor is Dr. Maruf Mortula. Available are both soft and hard copies of the thesis.